Regenerative Medicine Therapies for Targeting Neuroinflammation After Stroke - Rajkovic, Olivera; Potjewyd, Geoffrey; Pinteaux, Emmanuel (Frontiers in Neurology, 2018)
Inflammation is a major pathological event following ischemic stroke that contributes to secondary brain tissue damage leading to poor functional recovery. Following the initial ischemic insult, post-stroke inflammatory damage is driven by initiation of a central and peripheral innate immune response and disruption of the blood-brain barrier (BBB), both of which are triggered by the release of pro-inflammatory cytokines and infiltration of circulating immune cells. Stroke therapies are limited to early cerebral blood flow reperfusion, and whilst current strategies aim at targeting neurodegeneration and/or neuroinflammation, innovative research in the field of regenerative medicine aims at developing effective treatments that target both the acute and chronic phase of inflammation. Anti-inflammatory regenerative strategies include the use of nanoparticles and hydrogels, proposed as therapeutic agents and as a delivery vehicle for encapsulated therapeutic biological factors, anti-inflammatory drugs, stem cells and gene therapies. Biomaterial strategies – through nanoparticles and hydrogels – enable the administration of treatments that can more effectively cross the BBB when injected systemically, can be injected directly into the brain, and can be 3D-bioprinted to create bespoke implants within the site of ischemic injury. In this review, these emerging regenerative and anti-inflammatory approaches will be discussed in relation to ischemic stroke, with a perspective on the future of stroke therapies.